Election Management Bodies in West Africa - Madior Fall, Ismaila (African Minds, 2016)
This report is an in-depth study of electoral commissions in six countries of West Africa Benin, Cape Verde, Ghana, Nigeria, Senegal and Sierra Leone assessing their contribution in strengthening political participation in the region. As institutions that apply the rules governing elections, electoral management bodies (EMBs) have occupied, over the last two decades, the heart of discussion and practice on the critical question of effective citizen participation in the public affairs of their countries. The way in which they are established and the effectiveness of their operations have continued to preoccupy those who advocate for competitive elections, while reforms to the EMBs have taken centre stage in more general political reforms. Election Management Bodies in West Africa thus responds to the evident need for more knowledge about an institution that occupies a more and more important place in the political process in West Africa. Based on documentary research and detailed interviews in each country, the study provides a comparative analysis which highlights the similarities and differences in the structure and operations of each body, and attempts to establish the reasons for their comparative successes and failures.